Ministry of Civil Aviation Decree No. 607 of the Year 2015 Issued on 27/7/2015 = وزارة الطيران المدنى قرار رقم 607 لسنة 2015 الصادر فى 27/7/2015 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic